2009
DOI: 10.1055/s-0029-1218613
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of New Diversely Linked Biquinoline Derivatives by Multicomponent Imino-Diels-Alder Cycloaddition and Intramolecular Friedel-Crafts Cyclization

Abstract: New and efficient routes for diversely linked 2,6¢-, 2,7¢-, 2,2¢-, or 2,8¢-biquinoline derivatives are reported. These routes are based on the powerful methodologies of imino-Diels-Alder cycloaddition reactions and intramolecular Friedel-Crafts cyclization reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
(20 reference statements)
0
2
0
Order By: Relevance
“…Koutnezsov found that the environmentally friendly BiCl 3 is an excellent catalyst to trigger the three-component reaction between arylamines 597 , (hetero)­aryl aldehydes 598 , and N -vinylamides, including N -vinylacetamide 599 and N -vinylpyrrolidin-2-one 601 , to furnish cis -2,4-disubstituted THQs 600 and 602 in good to excellent yields (Scheme ). The same group subsequently employed this catalyst for the synthesis of other types of THQs. …”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
“…Koutnezsov found that the environmentally friendly BiCl 3 is an excellent catalyst to trigger the three-component reaction between arylamines 597 , (hetero)­aryl aldehydes 598 , and N -vinylamides, including N -vinylacetamide 599 and N -vinylpyrrolidin-2-one 601 , to furnish cis -2,4-disubstituted THQs 600 and 602 in good to excellent yields (Scheme ). The same group subsequently employed this catalyst for the synthesis of other types of THQs. …”
Section: Synthesis Of 1234-tetrahydroquinolines Via the Povarov Reactionmentioning
confidence: 99%
“…15,16 In addition to the aforementioned significance, polyquinolines possess n-type electrically conducting properties along with good thermal, mechanical, and oxidative attributes. 17,18 Although there are a few reports on the preparation of bicyclic quinolines, [19][20][21][22][23][24][25] most suffer drawbacks such as low yield, formation of by-products, the use of highly reactive coupling reagents, and competitive reductions in the presence of protonic sources. 26,27 To overcome these difficulties, we describe herein an efficient, one-pot synthesis of some new biquinoline/chromene-bearing quinoline systems linked through an aryl-aryl bond.…”
mentioning
confidence: 99%